2022
DOI: 10.1002/hpja.602
|View full text |Cite
|
Sign up to set email alerts
|

Interpersonal communication may improve equity in dementia risk education

Abstract: Issue addressed Encouraging people to adopt life‐long habits that reduce dementia risk is necessary to manage the growing global prevalence of this condition and is, therefore, a global health priority. Current initiatives promoting risk‐reducing behaviour primarily attract participants from a limited range of backgrounds, even if widely available. This may inadvertently increase health inequities, as the people who are most likely to develop dementia are the people who are least involved in risk‐reduction ini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 38 publications
(105 reference statements)
0
1
0
Order By: Relevance
“…Over 90% of responding participants affirmed that an interest in MOOC learning was among their reasons for enrolling in the course, indicating that this course is reaching a population that may be interested in MOOC learning more generally. Previous investigations in other MOOC participant populations have shown that information from MOOCs is shared through interpersonal communication, reaching more people from groups who are under-represented within the MOOC itself, especially men ( Fair et al ., 2023a , 2023b ). The information presented in the TBI MOOC may therefore likewise have additional reach beyond the population captured within this study.…”
Section: Discussionmentioning
confidence: 99%
“…Over 90% of responding participants affirmed that an interest in MOOC learning was among their reasons for enrolling in the course, indicating that this course is reaching a population that may be interested in MOOC learning more generally. Previous investigations in other MOOC participant populations have shown that information from MOOCs is shared through interpersonal communication, reaching more people from groups who are under-represented within the MOOC itself, especially men ( Fair et al ., 2023a , 2023b ). The information presented in the TBI MOOC may therefore likewise have additional reach beyond the population captured within this study.…”
Section: Discussionmentioning
confidence: 99%